Commentary on the Special Issue on Moral Injury: Unpacking Two Models for Understanding Moral Injury. Issue 3 (7th June 2019) - Nash, William P.
Abstract: The most robust finding of moral injury (MI) research thus far—that past exposure to potentially morally injurious events predicts current symptoms of posttraumatic stress disorder (PTSD)—challenges conceptions that trauma is exclusively the result of fear‐evoking brushes with death or sexual assault. It also calls into question the applicability to MI of treatments for PTSD grounded in the fear model of trauma. In the current article, two divergent theoretical models that have been applied to the understanding and treatment of moral injury are compared: the stress–appraisal–coping model and the stress injury model. Attention is drawn to the differences between how these models conceptualize stress and distress, including psychological trauma, and to their potential implications for the sustainment of mental health stigma, especially in military and veteran populations. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Desentrañando dos modelos para comprender el daño moral: Comentario para el número especial de Journal of Traumatic Stress sobre daño moral DOS MODELOS PARA ENTENDER EL DAÑO MORAL El hallazgo más robusto de la investigación sobre daño moral (DM) hasta el momento – que plantea que la exposición pasada a eventos potencialmente dañinos morales predice los síntomas actuales del trastorno de estrés postraumático (TEPT) ‐ desafía las concepciones de que el trauma es exclusivamente el resultado de una estructura del miedo asociado con la muerte o el asalto sexual. También pone en duda la aplicabilidad del DM en los tratamientos para el TEPT basados en el modelo de miedo del trauma. En el artículo actual, se comparan dos modelos teóricos divergentes que se han aplicado a la comprensión y el tratamiento del daño moral: el modelo de estrés‐evaluación‐afrontamiento y el modelo de daño por estrés. Se destaca acerca de las diferencias entre cómo estos modelos conceptualizan el estrés y la angustia, incluido el trauma psicológico, y sus posibles implicaciones para el mantenimiento del estigma asociado a la salud mental, especialmente en las poblaciones de militares y veteranos. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Unpacking Two Models for Understanding Moral Injury: Commentary for Journal of Traumatic Stress Special Issue on Moral Injury Traditional Chinese 標題: 說明兩個用以理解道德創傷的模型:創傷壓力期刊道德創傷特刊評論 撮要: 有關道德創傷(MI)的研究，最主要的發現為過去經歷潛在的道德創傷事件，可預測當前的創傷後壓力症(PTSD)症狀。然而，亦有說法指創傷只屬經歷死亡或性侵犯的威脅產生恐懼所致。以上兩種說法有所矛盾。此外，基於創傷的恐懼模型而生的PTSD療法是否適用於治療MI，亦成疑問。本文比較兩種不同、用以理解和治療MI的理論模型:壓力−評價−適應模型，及壓力受創模型。我們特別留意兩個模型如何概念化壓力與悲痛，當中包括心理創傷，以及兩個模型特別在現役及退役軍人中，潛在使心理健康污名持續的可能。 Simplified Chinese 标题: 说明两个用以理解道德创伤的模型:创伤压力期刊道德创伤特刊评论 撮要: 有关道德创伤(MI)的研究，最主要的发现为过去经历潜在的道德创伤事件，可预测当前的创伤后压力症(PTSD)症状。然而，亦有说法指创伤只属经历死亡或性侵犯的威胁产生恐惧所致。以上两种说法有所矛盾。此外，基于创伤的恐惧模型而生的PTSD疗法是否适用于治疗MI，亦成疑问。本文比较两种不同、用以理解和治疗MI的理论模型:压力−评价−适应模型，及压力受创模型。我们特别留意两个模型如何概念化压力与悲痛，当中包括心理创伤，以及两个模型特别在现役及退役军人中，潜在使心理健康污名持续的可能。